Broken Engagement: Teaching Finance during Pandemic Times. (May 2023) - Saravanan, Palanisamy; Banerjee, Sumit
Student engagement is critical to creating a collaborative and involved learning environment. The pandemic brought the class room engagement between the faculty and the students to a halt. We tried to find different avenues for the students to reach out to the faculty and to have an open forum to facilitate discussions among themselves. This approach helped us in increasing engagement and also allowed students who would normally not speak during the class hours to contribute to the overall learning during the course. JEL Codes: I20, I23, I29